1992
DOI: 10.1007/bf00004656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient ion concentrations on gill ATPases in fresh water eel,Anguilla anguilla

Abstract: Branchial activities of Na(+),K(+)-ATPase (ouabain sensitive), Mg(2+) ATPase (ouabain insensitive) and kinetic analysis of high and low affinity Ca(2+) ATPase were measured inAnguilla anguilla that had been acclimated to demineralized water (DW, Ca < 10 μM), freshwater (FW, Ca = 2 mM), and Low calcium freshwater (L-Ca, Ca = 0.9 mM). Na(+),K(+)-ATPase activity decreased while ouabain insensitive activity increased when ambient Ca(2+) decreased. Two kinetic forms of Ca(2+) ATPase could be resolved in each enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Na + ‐K + ATPase is a universal membrane‐bound enzyme that actively transports Na + out of and K + into animal cells. The biochemical mechanisms for maintenance of constant levels of ions in body fluids depend on the activity of Na + ‐K + ATPase, and the activities of gill Na + ‐K + ATPase in euryhaline teleosts are affected by environmental salinities and ion concentrations (Mayer‐Gostan & Naon ; McCormick et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Na + ‐K + ATPase is a universal membrane‐bound enzyme that actively transports Na + out of and K + into animal cells. The biochemical mechanisms for maintenance of constant levels of ions in body fluids depend on the activity of Na + ‐K + ATPase, and the activities of gill Na + ‐K + ATPase in euryhaline teleosts are affected by environmental salinities and ion concentrations (Mayer‐Gostan & Naon ; McCormick et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma chloride concentration decreased when salinity decreased, but this could result from levels and routes of exchange (compared to Na) through the different target organs involved in osmoregulation. Many euryhaline fish such as the eel Anguilla anguilla L., are considered as fully adapted to fresh water and often have very low plasma chloride concentrations (Mayer-Gostan & Naon, 1992), and a low plasma chloride concentration cannot be considered as an index of a physiological dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of this enzyme has been shown to vary significantly depending on the ionic composition of the environment. Not only is there an important difference between freshwater-and seawater-adapted fish (De Renzis & Bornancin, 1984;Venturini et al, 1992) but also in different freshwater compositions (Mayer-Gostan & Naon, 1992). Some investigations carried out on gills of fish adapted to a range of environmental salinities (Butler & Carmichael, 1972;Towle et al, 1977;Ip et al, 1991) suggested that the lowest activity of the gill enzyme occurs when the salinity of blood was close to that of the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mucus secretion has been noticed, which forms a coating on the gill surface of E. tirucalli latex exposed H. fossilis. The observed mucus coating cannot be linked to cause reduction of gill calcium permeability resulting in hypocalcemia as Part and Lock (1983) and Mayer-Gostan and Naon (1992) have reported that mucus is not a barrier to Ca 2þ . Thus, the impairment of net electrolyte influx either at the gill and/or renal function could be attributed to hypocalcemia observed in E. tirucalli latex exposed H. fossilis.…”
Section: Discussionmentioning
confidence: 94%